Caribbean Fruit Fly Management in Florida Peaches - Amanda Coleen Hodges; Cory Penca (EDIS)
The Caribbean fruit fly, Anastrepha suspensa, is a member of the fly family Tephritidae, which contains some of the most destructive fruit pests in the world. This 4-page fact sheet written by Amanda Coleen Hodges and Cory Penca and published by the UF/IFAS Department of Entomology and Nematology provides information about the biology and management of the Caribbean fruit fly. http://edis.ifas.ufl.edu/in1242